Stamp duties in Indian states : a case for reform - Alm, James, 1950- 1950- (Policy research working paper, 2004)
"Alm, Annez, and Modi review the options for reform of stamp duties on immovable property transfers collected by Indian state governments. After briefly reviewing some of the many administrative difficulties experienced with the tax, they turn to an examination of its economic impacts. A review of stamp duties internationally indicates that Indian rates are exceptionally high, at rates often above 10 percent. Most countries' rates are less than 5 percent, including a number of low and middle-income developing countries. With these high rates, the authors find that while the tax has become the third largest revenue source for many Indian states, it imposes high compliance costs on taxpayers, has been subject to a good deal of evasion and fraud, and the distortionary impacts appear to be large, reducing the responsiveness of real estate markets in Indian cities by discouraging transactions essential to the efficient growth of cities. The authors then study the revenue implications of lowering stamp duty rates, which need to be understood if reform is to be viable. Evidence indicates that the current high duty rates, coupled with weak tax administration, lead to widespread evasion of the tax through underdeclaration. This underdeclaration of property values directly affects collection of other taxes, among them, property taxes and capital gains tax. Moreover, it indirectly affects the collection of all taxes through the impact of underdeclaration on the circulation of black money. Simulations indicate that revenues lost due to a lowering of stamp duty rates closer to international levels are quite likely to be recovered in higher collections of other taxes. However, these taxes would at least in part be collected by other levels of government. So reform could be made a more viable option through appropriately designed intergovernmental transfers.